2018
DOI: 10.32413/pjph.v8i3.210
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Students Regarding the Formal Mentorship Programme for Medical Education

Abstract: Background: Medical students have a very extensive curriculum and a demanding time period during their undergraduate studies (1-5 years). Research has shown that medical students experience a high level of stress affecting their social, emotional as well as mental health. According to many studies formal mentoring is considered as a key to overcome these problems. Currently Khyber Pakhtunkhwa is deficient in formal mentorship program for medical education, the purpose of this article was to determine the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Regardless of the positive effect and advantages, previous studies findings did show that only one third of the respondents said that they have a bit knowledge about mentoring (12) (Abid et al, 2018). While in another study reported that students did not have past mentoring experiences (13).…”
Section: Mentoringmentioning
confidence: 88%
See 1 more Smart Citation
“…Regardless of the positive effect and advantages, previous studies findings did show that only one third of the respondents said that they have a bit knowledge about mentoring (12) (Abid et al, 2018). While in another study reported that students did not have past mentoring experiences (13).…”
Section: Mentoringmentioning
confidence: 88%
“…Data were collected through an online survey and disseminated using emails and WhatsApp medium platform. These platforms measured the following questionnaire that was adapted and modified from a validated questionnaire used in the study 'Knowledge and Attitude of Students Regarding the Formal Mentorship Programme for Medical Education' (12). This questionnaire consists of three parts; Part A: sociodemographic of the participants which include age, gender, year of study and the interaction of the participants with their mentor.…”
Section: Methodsmentioning
confidence: 99%